Velocity-map imaging with counter-propagating laser pulses - Heldt, Tobias; Oelmann, Jan-Hendrik; Guth, Lennart; Lackmann, Nick; Pfeifer, Thomas; Crespo López-Urrutia, José Ramon (Optics letters, 2024)
Velocity-map imaging (VMI) is a key tool for studying outgoing electrons or ions following optical strong-field interactions of atoms and molecules and provides good momentum resolution even if the source volume of the fragments extends along a laser beam path. Here, we demonstrate within an enhancement cavity how, independently of the focal Rayleigh length, counter-propagating pulses longitudinally compress the ionization volume down to few tens of micrometers. We observe nonlinear above-threshold ionization (ATI) processes confined to the spatial overlap of femtosecond pulses, whereas the shortened ionization volume makes an electrostatic lens unnecessary for VMI.